Desempenho de pontas de pulverização na deposição de gotas de pulverização na cultura do amendoim - Rodrigues da Costa, Andreia Cristina Peres; Martins, Dagoberto [UNESP]; da Costa, Neumarcio Vilanova; Rocha Pereira, Maria Renata; Cardoso da Silva, Jose Iran (Universidade Estadual de Londrina (UEL), 2011)
The objective of this study was to evaluate the effect of nozzles on spray droplet deposition in the peanut crop cultivar 'Runner IAC 886'. The study was conducted in the field, and the applications of treatments performed in the vegetative stage (V1) and reproductive (R2). It was used the Brilliant Blue FDC - 1 as tracer in water solution, at 500 ppm. The treatments consisted of seven spray nozzle XR 110015 VS (150 L ha(-1)), XR 11002 VS (200 L ha(-1)), TX-VK 6 (150L ha(-1)), TX-VK 8 (200 L ha-1), AI 110015 VS (150 L ha(-1)), AI11002 VS (200 L ha(-1)) e TJ60 11002 VS (150 e 200 L ha(-1)). It was used a randomized blocks design, with four replications. After application, plants were immediately collected, and washed in 100 mL of distilled water for posterior tracer quantification in spectrophotometer. The data had been adjusted a regression curve for Gompertz model. The results had evidenced that at low volumes of application the nozzle AI 110015 VS and TJ60 11002 VS, were the ones with best distribution uniformity of spray on plants of peanut cultivar 'Runner IAC 886' in the vegetative stage (V1) and reproductive (R2) respectively, and the largest deposits and higher percentage of failures in applications have been found in younger plants by comparing the growth stages of application, regardless of the spray nozzle and volume.
Spray nozzles performance in the deposition of spray droplets on peanut crop
Keywords: Spray nozzle; application technology; uniformity of deposition